Analisis Pengaruh Modal Dan Biaya Produksi Terhadap Pendapatan UMKM - Wafiroh, Hibatin; Lailatul, Ika Nur; Evhin, Ainayyah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
SMEs are important in the country’s economy, especially in Indonesia today. Because it started with a large number of layoffs at large companies causing people’s income to be hampered; from this problem, many people have opened medium-sized businesses for the survival of their lives. From these events, the government participated in helping SMEs in the vicinity to restore the country’s current economy. However, several obstacles exist in these SMEs, such as a lack of capital and increased production costs. In this study, capital and production costs can significantly affect income. In processing the data, we use the SPSS application to analyze the effect of the independent and dependent variables. The results of the study show that production costs affect SMEs’ income. Capital for SMEs for operational activities makes working capital important but could be more influential in increasing income.